2008
DOI: 10.1007/s12185-008-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of adult Langerhans cell histiocytosis showing successfully regenerated osseous tissue of the skull after chemotherapy

Abstract: Langerhans cell histiocytosis (LCH) is a proliferative disorder of Langerhans cells and extremely rare in adults. Adult LCH is often associated with osteolytic bone lesions, but large bone-defective lesions have been rarely reported. We report an adult case of LCH accompanied by large osteolytic lesions in the skull that successfully responded to chemotherapy. A 47-year-old woman with LCH who had multiple, large osteolytic areas of more than 3 cm in diameter in the skull was admitted to our hospital. She was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The few data available concerning vinblastine treatment in adult LCH patients mainly concern patients with bone disease [11, 2123]. Individual case reports showed a rather good response to vinblastine [2123].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few data available concerning vinblastine treatment in adult LCH patients mainly concern patients with bone disease [11, 2123]. Individual case reports showed a rather good response to vinblastine [2123].…”
Section: Discussionmentioning
confidence: 99%
“…Individual case reports showed a rather good response to vinblastine [2123]. In contrast, in a series of adult patients with bone disease, [11] found that 84% patients treated with vinblastine had a poor response, defined by either the absence of response or relapse of LCH within a year.…”
Section: Discussionmentioning
confidence: 99%
“…The whole liver of this patient was hypodense on CT images, as previously reported. 13 The patient had never drunk alcohol, and laboratory tests ruled out viral hepatitis (hepatitis A, B, and C, Epstein-Barr virus, and cytomegalovirus) and autoimmunerelated diseases. Thus, nonalcoholic fatty liver disease (NAFLD) was considered, which caused the hepatic failure, in addition to LCH infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] On the other hand, in adult cases, optimal treatment has not been established, and the treatment strategy is employed referring to child cases. [4][5]8,12,13 We herein present a case of adult-onset MS-LCH, which rapidly progressed to multi-organ failure after steroid reduction and showed no improvement despite combination chemotherapy.…”
Section: Introductionmentioning
confidence: 95%
“…Hasta steroid tedavisine yanıtsızsa, progresyon gösteriyorsa ve çoklu organ tutulumu varsa diğer tedavi seçe-neklerinin (etoposid, vinblastin, metotreksat, siklofosfamid, siklosporin, talidomid gibi) denenebileceğine dair yayınlar vardır. 11 Kadın hastamız aksiller lenf bezi tutulumu ve solunum fonksiyon testlerinde bozulma nedeniyle evre II kabul edilmiş ve 0,5 mg/kg/gün dozda sistemik steroid tedavisi başlatılmıştır. Erkek hastamız ise izole PLHH'dir ve sadece solunum fonksiyon testlerinde bozulma vardır.…”
Section: Resim 3 1x100 H-e Boyamaunclassified